2009
DOI: 10.1098/rsif.2009.0295.focus
|View full text |Cite
|
Sign up to set email alerts
|

A schlieren optical study of the human cough with and without wearing masks for aerosol infection control

Abstract: Various infectious agents are known to be transmitted naturally via respiratory aerosols produced by infected patients. Such aerosols may be produced during normal activities by breathing, talking, coughing and sneezing. The schlieren optical method, previously applied mostly in engineering and physics, can be effectively used here to visualize airflows around human subjects in such indoor situations, non-intrusively and without the need for either tracer gas or airborne particles. It accomplishes this by rend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
294
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(328 citation statements)
references
References 56 publications
16
294
0
4
Order By: Relevance
“…We do not believe that higher-level respirator use by patients with TB is warranted for this purpose due to cost and discomfort (38). Moreover, whereas a better face seal can reduce leakage around the filtration piece of a respirator during inspiration, it is unlikely to substantially resist the air pressure generated by cough, and air is likely to escape around either a surgical mask or respirator, as illustrated by others using real-time optical imaging of air flow patterns during cough (39). The purpose of a surgical mask, like a hand or tissue, is not to contain the cough but to stop the exit of a portion of the larger droplets otherwise destined to become droplet nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…We do not believe that higher-level respirator use by patients with TB is warranted for this purpose due to cost and discomfort (38). Moreover, whereas a better face seal can reduce leakage around the filtration piece of a respirator during inspiration, it is unlikely to substantially resist the air pressure generated by cough, and air is likely to escape around either a surgical mask or respirator, as illustrated by others using real-time optical imaging of air flow patterns during cough (39). The purpose of a surgical mask, like a hand or tissue, is not to contain the cough but to stop the exit of a portion of the larger droplets otherwise destined to become droplet nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 illustrates the physical picture that emerges from a synthesis of our flow visualizations, prior work on cloud visualization using schlieren (e.g. Tang et al 2009) and droplet sampling (e.g. Morawska et al 2009b).…”
Section: Black Feltmentioning
confidence: 99%
“…Although Tang et al (2009) have shown with Schlieren airflow imaging that wearing both surgical and N95 masks should be effective in containing infectious aerosols produced by the wearer, there are many complex issues surrounding mask-wearing. First, there is the actual physical filtering effectiveness of the mask in blocking the passage of bacteria and viruses.…”
Section: Mitigating Transmissionmentioning
confidence: 99%
“…Natural means include breathing, talking, sneezing, singing and, in particular, coughing. In this volume, coughing is explored using an artificial cough machine by Pantelic et al (2009) and using human volunteers by Xie et al (2009) and Tang et al (2009). Artificial means of producing potentially infectious aerosols are abound in hospitals, particularly when taking high-risk respiratory samples S698 I. Eames et al Airborne transmission of disease like nasopharyngeal aspirates or when using respiratory assist equipment, such as nebulizers (Hui et al 2009), ventilators (Hui et al 2006a,b) or oxygen masks (Hui et al 2006a(Hui et al ,b, 2007Ip et al 2007) for patients in respiratory distress.…”
Section: Generation Of Fomites In the Air And Their Microbiological Cmentioning
confidence: 99%